2020
DOI: 10.1111/iwj.13446
|View full text |Cite
|
Sign up to set email alerts
|

Foot care knowledge, attitudes and practices among patients with diabetic foot and amputation in St. Kitts and Nevis

Abstract: About one‐third of admissions to the surgical unit annually are diabetes foot infections in need of amputation In St. Kitts and Nevis. However, the risk factors related to diabetes foot and amputation remain unknown. This study investigated factors associated with diabetic foot and amputation (DFA). Retrospective case control study design, and purposive and quota sampling method was used to recruit the participants. Patients with and without DFA were interviewed at two main hospitals, several primary health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…It is known that foot care involves more than performing care tasks, highlighting the knowledge, attitudes and practices of patients with diabetic and amputated feet. 20,21 Family, economic, and working conditions, along with health system-related factors are the most important elements in the care of patients with diabetes and amputations. 20 In fact, support from family members and friends can be an important source of self-management support, 21 and can putatively explain our findings regarding the difference in the more positive diet when considering marital status comparing patients who live with or without a partner, since forty-four percent of US adults help a family member or friend with chronic disease management and another 9% are willing to start.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that foot care involves more than performing care tasks, highlighting the knowledge, attitudes and practices of patients with diabetic and amputated feet. 20,21 Family, economic, and working conditions, along with health system-related factors are the most important elements in the care of patients with diabetes and amputations. 20 In fact, support from family members and friends can be an important source of self-management support, 21 and can putatively explain our findings regarding the difference in the more positive diet when considering marital status comparing patients who live with or without a partner, since forty-four percent of US adults help a family member or friend with chronic disease management and another 9% are willing to start.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Family, economic, and working conditions, along with health system-related factors are the most important elements in the care of patients with diabetes and amputations. 20 In fact, support from family members and friends can be an important source of self-management support, 21 and can putatively explain our findings regarding the difference in the more positive diet when considering marital status comparing patients who live with or without a partner, since forty-four percent of US adults help a family member or friend with chronic disease management and another 9% are willing to start. 21,22 The logistic regression analysis showed that Marital Status presented significance (p=0.028) in item 2: Specific Food, for sub-item 2.2: Eating high-fat food meat and/or whole milk products and a tendency (p=0.058) for sub-item 2.3: Eating sweets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is becoming more common with each passing year, with the number of people living with diabetes expected to rise 1.5 fold from 463 million in 2019 to 700 million in 2045. Diabetic foot ulcers, one of the most serious complications of diabetes, macrovascular disease and microvascular damage accompanied by neuropathy and ischemic problems, which facilitates the development of infection, ulcer and gangrene and eventually causes morbidity and mortality, is a difficult, long and costly health problem [1,2]. The global prevalence of diabetic foot ulcers has been reported to be 6.3% [3].…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of diabetic foot ulcers has been reported to be 6.3% [3]. Individuals' quality of life suffers as a result of complications caused by diabetic foot ulcers, as well as a rise in mortality and a physical, psychological, and economic burden [2,4,5].…”
Section: Introductionmentioning
confidence: 99%